Thoughts on the demise of FDI - Ronald B. Davies (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
This essay addresses the recent deceleration in the pace of global FDI and asks whether multinational corporations are actually in retreat. It identifies the forces that are slowing the expansion of FDI, and sketches the role that multinational corporations will play in the future.
Keywords: F21; F23; 330; foreign direct investment; multinational corporations